2005
DOI: 10.2169/internalmedicine.44.251
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo (Ampulla-shaped) Cardiomyopathy Associated with Microscopic Polyangiitis

Abstract: Recently, a cardiac disorder characterized by ballooning and hypokinesis at the apex has been described as takotsubo (ampulla-shaped) cardiomyopathy. We encountered a patient with a rare case of takotsubo cardiomyopathy associated with microscopic polyangiitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
(16 reference statements)
1
16
0
Order By: Relevance
“…Treatment with an anti-inflammatory agent was remarkably effective for the systemic inflammation and focal cardiac damage in the case of Sato et al (12). We speculate that the treatment may have suppressed the excessive secretion of various cytokines.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…Treatment with an anti-inflammatory agent was remarkably effective for the systemic inflammation and focal cardiac damage in the case of Sato et al (12). We speculate that the treatment may have suppressed the excessive secretion of various cytokines.…”
mentioning
confidence: 66%
“…Sato et al (12) published what we believe to be the first report of a case of takotsubo cardiomyopathy associated with microscopic polyangiitis. Based on their experience with this very rare case, they concluded that microscopic polyangiitis might be a causative factor of this disease.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…In these reports, inflammatory infiltrates and myocyte necrosis were revealed in microscopic examination. There is a report of a case of ampulla cardiomyopathy associated with microscopic polyangiitis [22]. In that case, a large amount of steroid was effective.…”
Section: Discussionmentioning
confidence: 99%